Economic culture of the population of Belarus and Russia as the basis of integration processes - Gavrilik, Oksana N. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article presents the results of a comparative study of the economic culture of the population of Belarus and Russia on the basis of the data of two international studies – the project «European Values Study» (wave 2008–2009) and the study of A. M. Sidorova economic mentality of the population of different countries by the method of Hofstede. It is the use of common indicators in sociological measurements that has become a reliable basis for comparative analysis. The conclusion is made about the proximity of the value orientations of the population of Belarus and Russia in the economic sphere, which is one of the most important factors of the success of the integration processes between the these countries.
Keywords: economic culture; economic mentality; economic behavior; integration processes